Edukasi Karakter Berbasis Tri Hita Karana Program Studi Pendidikan Agama Hindu di Pura Anggreka Sari: Pengabdian - Ayu Widha Erlia; Gusti Ayu Nanik Ardhiani; Ni Putu Diah Untari Ningsih; I Ketut Dani Budiantara; I Wayan Gama (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community service program aims to implement character education based on Tri Hita Karana at Pura Anggreka Sari and to examine its impact on changes in community attitudes and behaviors. The study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The program was conducted in three stages: planning, implementation, and evaluation with follow-up. The planning stage focused on identifying community needs and developing educational materials grounded in the values of parahyangan, pawongan, and palemahan. The implementation stage involved socialization, group discussions, and direct practice integrated into religious and social activities. The evaluation stage assessed behavioral changes among participants and included reflective sessions to determine appropriate follow-up actions. The results indicate that character education based on Tri Hita Karana enhances participants’ understanding and promotes positive changes in spiritual attitudes, social interactions, and environmental awareness. Field findings reveal increased participation in religious activities, improved social cohesion, and greater concern for environmental sustainability within the temple area. However, several challenges were identified, including limited implementation time and inconsistent application of values in daily life. Strong support from temple authorities and active community participation were key factors contributing to the program’s success. In conclusion, Tri Hita Karana-based character education is effective in fostering holistic and contextual character development within the community. This program has the potential to serve as a sustainable community service model, particularly when supported by continuous mentoring and strengthened community-based initiatives.